Estradiol-17β increases 12- and 15-lipoxygenase (type2) expression and activity and reactive oxygen species in human umbilical vascular smooth muscle cells. Issue 163 (October 2016) - Somjen, Dalia; Kohen, Fortune; Limor, Rona; Sharon, Orli; Knoll, Esther; Many, Ariel; Stern, Naftali
Highlights: E2 increased 12 and 15LO mRNA expression by 2–3 folds and elicited an acute 50% increase 12 and 15HETE production. Neither ERα nor ERβ-specific agonists induce LO expression. E2-induced expression was blocked by ER non-specific and receptor subtype specific antagonists. E2 as well as 12 and 15HETE increased reactive oxygen species (ROS) in VSMC. E2-dependent and HETE-induced ROS could be blocked by NAD (P) H-oxidase inhibitors and by the ER non-specific antagonist ICI. E2- but not HETE- induced ROS was partially blocked by the LO inhibitor baicalein. Abstract: The net vascular effect of estrogens on the vasculature is still under debate. Here we tested the effects of estradiol- 17β (E2) as well as estrogen-receptor subtype specific and non-specific agonists and antagonists on the expression and eicosanoid production of lipoxygenase (LO) enzymes expressed in culture human umbilical vascular smooth muscle cells (VSMC), the platelet type 12LO and 15LO type 2. E2 increased 12 and 15LO mRNA expression by 2–3 folds and elicited an acute 50% increase 12 and 15 hydroxyeicosatetraenoic acid (HETE) production. Neither estrogen receptor ERα nor ERβ-specific agonists were able to reproduce the induction of LO expression, but E2-induced expression was effectively blocked by ER non-specific and receptor subtype specific antagonists. Because 12 and 15HETE can increase reactive oxygen species in other cell types, we tested the possibility that E2 could raise ROS through LO. Indeed, E2 as well as the LO products 12 and 15HETE increased reactive oxygen species (ROS) in VSMC. E2-dependent and HETE-induced ROS could be blocked by NAD (P) H-oxidase inhibitors and by the ER general antagonist ICI. E2-induced ROS was partially (∼50%) blocked by the LO inhibitor baicalein, but the LO blocker had no effect on 12 or 15HETE- induced ROS formation, thus suggesting that part of E2-dependent ROS generation resulted from E2-induced 12 and 15HETE. Collectively these findings unveil an unrecognized effect of E2 in human VSMC, to induce 12 and 15LO type 2 expression and activity and suggest that E2-dependent ROS formation in VSMC may be partially mediated by the induction of 12 and 15HETE.